2005
DOI: 10.1021/jo050724z
|View full text |Cite
|
Sign up to set email alerts
|

Phosphine-Free Palladium Acetate Catalyzed Suzuki Reaction in Water

Abstract: Pd(OAc)(2) in a mixture of water and poly(ethylene glycol) (PEG) is shown to be an extremely active catalyst for the Suzuki reaction of aryl iodides and bromides. The reaction can be conducted under mild conditions (50 degrees C) without the use of a microwave or phosphine ligand in high yields. The isolation of the products is readily performed by the extraction of diethyl ether, and the Pd(OAc)(2)-PEG can be reused without significant loss in activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
63
0
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 205 publications
(71 citation statements)
references
References 58 publications
7
63
0
1
Order By: Relevance
“…The process can be dependent upon the reaction medium, oxygen, moisture and additives/ stabilizers. A plethora of additives/stabilizers has been reported for 'ligandless' SM reactions, 21,23,[25][26][27][28] but this is not always necessary; we 29 and others 17,24 have shown that Pd(OAc) 2 alone is sufficient for high turnovers. Notably, these reactions occur in protic solvents such as alcohols, ethylene glycol derivatives, or mixtures of water with organic solvents.…”
Section: Introductionmentioning
confidence: 83%
“…The process can be dependent upon the reaction medium, oxygen, moisture and additives/ stabilizers. A plethora of additives/stabilizers has been reported for 'ligandless' SM reactions, 21,23,[25][26][27][28] but this is not always necessary; we 29 and others 17,24 have shown that Pd(OAc) 2 alone is sufficient for high turnovers. Notably, these reactions occur in protic solvents such as alcohols, ethylene glycol derivatives, or mixtures of water with organic solvents.…”
Section: Introductionmentioning
confidence: 83%
“…The resulting residue was redissolved in CDCl 3 and the yield was calculated by 1 H-NMR using diethylene glycol dimethyl ether as internal standard. Following this procedure the following products were prepared: 1-Biphenyl-4-yl-ethanone (5ª) 13 (>99%, chromatographically pure, 99% isolated yield) 4-Methoxybiphenyl (5d) 13 (60%) 3-Methoxybiphenyl (5e) 14 (11%). 13 (6%) generous donation of hexane.…”
Section: Hiyama Coupling Catalyzed By Pincer Complex 2 (Methods B) Gementioning
confidence: 99%
“…Following this procedure the following products were prepared: 1-Biphenyl-4-yl-ethanone (5ª) 13 (>99%, chromatographically pure, 99% isolated yield) 4-Methoxybiphenyl (5d) 13 (60%) 3-Methoxybiphenyl (5e) 14 (11%). 13 (6%) generous donation of hexane. Finally, technical and human support provided by SGIker (UPV/EHU, MICINN, GV/EJ, ESF) is acknowledged.…”
Section: Hiyama Coupling Catalyzed By Pincer Complex 2 (Methods B) Gementioning
confidence: 99%
See 1 more Smart Citation
“…However, there are still several problems with these complexes heterogeneous catalysis systems, including the expatiatory synthetic route and high cost [16,17]. Consequently, there is a strong interest in developing 'ligandless' Pd catalysts [18][19][20], and some ligandless supported catalysts have been developed in Suzuki reaction [21,22]. The choice of the support is critical to formulate an effective immobilization strategy because of the support influences the catalytic behavior of immobilized catalysts obviously [23].…”
Section: Introductionmentioning
confidence: 99%